Facilitating Assessments to Foster 21st Century Skills:Towards Technological Terrains - Wadhwa, Sujata; Barlow, Audre; Jadeja, Siddharthsinh (Journal of Engineering Education Transformations, 2016)
With the shift from industrial age to the information age, a subsequent transformation can also be witnessed, especially in engineering education, from the traditional education system to outcome based education i.e. OBE. Computers has almost eliminated human efforts to do the routine repetitive work and hence non routine problem solving skill and other 21st century skills are demanded from the graduates, specifically from engineers.The essence of OBE is 'success for all" by empowering all the students with skills and opportunities. There are already indications that there is a considerable gap between what is expected from an engineering graduate and what is offered. This gap will considerably widen unless learning outcomes, classroom practices, learning and assessment methods are coherently crafted and implemented so as to facilitate a flexible, personalized and significantly meaningful experience for the student[1]to succeed in the workplace of 21st century. Despite technology being the lifeblood of 21st century and the availability of smartphones with teachers and almost all the students, the problem of individual interaction and one-to-one assessment is prevalent. This research study explores technology to enhance students' engagement in the learning process to promote the inculcation of 21st century skills and facilitate the development of life-long learning. The authors also propose personal assessment and peer feedback, at regular intervals, followed by the mentor feedback and experts' comments. The authors also propose personal assessment and peer feedback, at regular intervals, followed by the mentor feedback and experts' comments as the best tool of inculcating and continuously assessing the 21st century skills essentially required among the fresh engineers.